A longitudinal study on the early development of leader-member exchanges. - Liden, Robert C.; Wayne, Sandy J.; Stilwell, Dean (Journal of Applied Psychology, 1993)
All in-text references underlined in blue are linked to publications on ResearchGate, letting you access and read them immediately.